(untitled) (Research, Society and Development, 2020)
Coronary Artery Disease predisposes to the development of ischemic heart disease, being one of the main causes of morbidity and mortality worldwide. Percutaneous coronary interventions revascularize the myocardium through the implantation of stents in order to restore blood flow in the affected arteries. Due to the high use of these devices in percutaneous procedures, as well as the currently found limitations, such as stent thrombosis, restenosis and adverse cardiac events, the aim of the present study was to analyze publications that deal with the different generations of stents in the treatment of arterial disease coronary, through a literary review, with a search in Scielo, Pubmed and Sciencedirect databases. Drug-eluting stents have emerged as a safer and more effective alternative than conventional stents, reducing episodes of restenosis and major adverse cardiac events. However, an increased risk of thrombosis linked to its use was observed. Thus, by improving the design, as well as the materials used in its manufacture, several generations of drug-eluting stents were developed, expanding the therapeutic collection. Despite this, further studies are still needed to prove its long-term safety.